2013
DOI: 10.1038/nrclinonc.2013.217
|View full text |Cite
|
Sign up to set email alerts
|

End-of-life care—what do cancer patients want?

Abstract: Patients with cancer frequently suffer from debilitating physical symptoms and psychological distress, particularly at the end of life. Interventions to help alleviate these problems are often complex and multifactorial. Palliative care services and therapeutic interventions have developed in a variable manner, often with limited evaluation of clinical effectiveness and affordability, resulting in a relatively weak evidence base. The health care provided to patients with advanced-stage cancer does not always c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
65
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(70 citation statements)
references
References 79 publications
3
65
0
2
Order By: Relevance
“…Nonetheless, the percentage of hospice recipients enrolled in hospice for 7 days or less has remained around 30% despite many efforts to encourage earlier entry into hospice. 3 Some suggest that the terrible choice inherent in Medicare’s requirement to essentially give up further disease-modifying treatment is 1 reason that many patients enter hospice so late. 4,5 Studies of palliative care for patients with cancer provided before hospice, including at the time of diagnosis with late-stage disease, have repeatedly revealed improved patient outcomes, including earlier hospice referral and lower costs relative to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, the percentage of hospice recipients enrolled in hospice for 7 days or less has remained around 30% despite many efforts to encourage earlier entry into hospice. 3 Some suggest that the terrible choice inherent in Medicare’s requirement to essentially give up further disease-modifying treatment is 1 reason that many patients enter hospice so late. 4,5 Studies of palliative care for patients with cancer provided before hospice, including at the time of diagnosis with late-stage disease, have repeatedly revealed improved patient outcomes, including earlier hospice referral and lower costs relative to usual care.…”
Section: Discussionmentioning
confidence: 99%
“…8,9 Our study addresses this gap in care by linking inpatient palliative care consultations to hospice use, especially at the time of death, when its resources are so crucial not only to patients, but also to their family members and caregivers. Hospice still remains an underused resource despite its demonstrated ability to improve quality of care and patient satisfaction and reduce costs.…”
Section: Discussionmentioning
confidence: 99%
“…The US National Institutes of Nursing Research does a lot of research on end-of-life issues and have identified the following research gaps: living with uncertainty; the costs of caregiving; communication; interventions for ethnically and culturally diverse populations; and transitions in care. 214,215 We have much to learn from our patients 216,217 and our European colleagues 218 in this area. Although some foundations fund end-of-life research, 219 overall federal funding for end-of-life research is small and should be expanded.…”
Section: Supportive Carementioning
confidence: 97%